2019
DOI: 10.1039/c9sm00570f
|View full text |Cite
|
Sign up to set email alerts
|

The intimate relationship between cavitation and fracture

Abstract: Nearly three decades ago, the field of mechanics was cautioned of the obscure nature of cavitation processes in soft materials [Gent, A.N., 1990. Cavitation in rubber: a cautionary tale. Rubber Chemistry and Technology, 63 (3)]. Since then, the debate on the mechanisms that drive this failure process is ongoing. Using a high precision volume controlled cavity expansion procedure, this paper reveals the intimate relationship between cavitation and fracture. Combining a Griffith inspired formulation for crack pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 53 publications
(74 reference statements)
0
41
0
Order By: Relevance
“…For example, we anticipate that one can extend cavitation techniques (e.g. [3,19]), to measure the critical cavitation pressure, P c , as a function of cavity size during growth, and thus allow the testing of the hypothesis in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we anticipate that one can extend cavitation techniques (e.g. [3,19]), to measure the critical cavitation pressure, P c , as a function of cavity size during growth, and thus allow the testing of the hypothesis in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Although cavitation and fracture are different physical processes, differentiating them and understanding their interrelationship have been challenging (40,(43)(44)(45)(46). For soft solids, the question of whether critical deformations are associated with cavitation or fracture is highly relevant for many applications, such as materials characterization (17,47,48), design of pressuresensitive adhesives (42,49,50), and understanding damage of biological tissues (3).…”
Section: Cavitation Mechanics and Dynamicsmentioning
confidence: 99%
“…Zhu et al (72) demonstrated the importance of loading conditions by altering the initial stiffness of the instrument to be either compliant (i.e., fixed pressure conditions) or stiff (i.e., fixed volume) loading conditions. Raayai-Ardakani et al (48,62) have recently exploited fixed volume conditions to characterize materials properties before and after the critical event to develop a method well suited for characterizing materials stiffer than those typically tested with pressure-controlled systems.…”
Section: A B Cmentioning
confidence: 99%
“…B/A → ∞) then λ b → 1. It was previously shown that within the range 1 < λ < 1.8, the cavity expansion response of NH bodies of B/A > 10 are nearly identical [46,47]. The response of soft materials are described by various constitutive formulations, generically written based on the deformation gradient or simplified in terms of the principal stretches or the invariants of the Cauchy Green strain tensor.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The applicability of VCCE was confirmed in soft PDMS (polydimethylsiloxane) samples, for which the neo-Hookean (NH) constitutive model is able to provide a reliable representation of the material behavior prior to failure. Later, in [47], it was shown that using this volume controlled technique one can track the intertwined process of cavitaiton and fracture to obtain insight on the specific failure mechanism. The VCCE method was introduced to complement the Cavitation Rheology (CR) technique invented by Crosby and coworkers [48-51, 35, 52-54] by removing the need for a priori assumptions on the constitutive response and the failure mechanism.…”
Section: Introductionmentioning
confidence: 99%